Two channel quantum security modelling focusing on quantum key distribution technique - Abubakar, M.Y. (Institute of Electrical and Electronics Engineers Inc., 2015)
The work presents in this paper proposes to solve the existing issue of initial qubit (primary key) lost due to an attack by eavesdropper, causing the quantum bit error rate (QBER) to be high which may leaked enough information to the eavesdropper during secret key sharing in network communication. We intend to greatly reduce the QBER to a reasonable percentage that will make the key sharing communication more secured and effective. We use the dual quantum channels against the traditional single quantum channel. The dual channels give an upper hand to reduce the chances of error caused by eavesdropper. Simulations were conducted for varying the noise factor which is a measure of the presence of an eavesdropper. The results where compared between our proposed method and the one quantum channel model. Our method shows an almost half of the QBER reduced during the secret key sharing session. Â© 2015 IEEE.